Diversity and evolutionary dynamics of spore-coat proteins in spore-forming species of Bacillales. Issue 11 (14th November 2020) - Secaira-Morocho, Henry; Castillo, José A.; Driks, Adam
Abstract : Among members of the Bacillales order, there are several species capable of forming a structure called an endospore. Endospores enable bacteria to survive under unfavourable growth conditions and germinate when environmental conditions are favourable again. Spore-coat proteins are found in a multilayered proteinaceous structure encasing the spore core and the cortex. They are involved in coat assembly, cortex synthesis and germination. Here, we aimed to determine the diversity and evolutionary processes that have influenced spore-coat genes in various spore-forming species of Bacillales using an in silico approach. For this, we used sequence similarity searching algorithms to determine the diversity of coat genes across 161 genomes of Bacillales. The results suggest that among Bacillales, there is a well-conserved core genome, composed mainly by morphogenetic coat proteins and spore-coat proteins involved in germination. However, some spore-coat proteins are taxa-specific. The best-conserved genes among different species may promote adaptation to changeable environmental conditions. Because most of the Bacillus species harbour complete or almost complete sets of spore-coat genes, we focused on this genus in greater depth. Phylogenetic reconstruction revealed eight monophyletic groups in the Bacillus genus, of which three are newly discovered. We estimated the selection pressures acting over spore-coat genes in these monophyletic groups using classical and modern approaches and detected horizontal gene transfer (HGT) events, which have been further confirmed by scanning the genomes to find traces of insertion sequences. Although most of the genes are under purifying selection, there are several cases with individual sites evolving under positive selection. Finally, the HGT results confirm that sporulation is an ancestral feature in Bacillus .